Erodibility of soil above the groundwater level: some test results - Shidlovskaya Anna; Briaud Jean-Louis; Chedid Mabel; Keshavarz M. (E3S Web of Conferences, 2016)
The paper presents a study on erodibility of soil above the groundwater level where the water is in tension. Such soils particularly clays are very sensitive to moisture and temperature changes and can be eroded significantly by water flow. The erosion of clay and sand samples from the US National Geotechnical Experimentation Site at Texas A&M University is studied. Two sets of experiments are done with the clay and the sand. The first set was performed on sample collected in November 2014 and the second set on samples from June 2014. The depth of the samples varied from 0.6 to 3.6 m where water content and density changes. A series of erosion tests was performed in the Erosion Function apparatus (EFA) with the intact clay and then with the sand reconstructed to the field density and field water content. The erosion tests are performed at different flow velocities varying from 0.5 m/s to 5.5 m/s. The erodibility is quantified by the relationship between the erosion rate and the water velocity called the erosion function. Some relationships between the critical velocity and common soil properties are discussed. The collapse of the clay structure when inundated (soaking) is studied.